Drug Abuse Prevention to Increase Prevention Knowledge for Vocational High School Students - Ash-Shiddiqy, Ahmad Rifqy (Bisma The Journal of Counseling, 2024)
The high rate of drug abuse among adolescents and the limited number of effective learning modules for the prevention of drug abuse are crucial and urgent problems to be overcome at this time. This study aims to develop and test the effectiveness of the drug abuse prevention module in increasing the knowledge of vocational high school students, so that it can contribute to more effective prevention efforts in the school environment. The method used in this study is an experimental method with a pretest-posttest control group design, which allows researchers to measure the impact of module use on improving students' knowledge objectively. The research subjects consisted of 50 students who were selected by purposive sampling from several vocational high schools. The data collection technique was carried out through pretest and posttest, which was then analyzed using dependent and independent t-tests to measure significant differences between the control group and the experiment. The results showed that the use of modules significantly increased students' knowledge about drug abuse prevention, indicating that the modules developed were effective as teaching materials. The implications of this study are the importance of integrating comprehensive, up-to-date, evidence-based prevention modules in school Guidance and Counselling programs to prevent drug abuse among adolescents, as well as the need for further development to extend its impact to a variety of other educational contexts.